Coronavirus pandemic and its impacts on the world’s economy - Muhammad Suleman Nasir; Muhammad Qayyum Ahsan (Goodwood Publishing, 2023)
Purpose: This study is about the coronavirus pandemic and its long-lasting impacts on the world economy. The study's main purpose is to highlight the adverse effects of the Coronavirus on the world's economy and how to mitigate it. Research Methodology: An analytical and descriptive research methodology was conducted to get findings and recommendations. Original material is obtained from primary sources. Information is also taken from books on websites and previous articles on the subject. Results: Precautions and impacts are presented, followed by the recommendations to diminish the effects of Coronavirus. Limitations: The impacts of Coronavirus are not limited to developing countries, but this study has given less focus to developed countries. Contribution: This study is helpful to understand the impacts and redefine the course of actions accordingly. Keywords: Covid-19, Symptoms, Precautions, Economic effect